EL NACIMIENTO DE LA PRENSA DE EMPRESA EN ANDALUCÍA DURANTE LA RESTAURACIÓN. ANÁLISIS ESTRUCTURAL DE LA PROPIEDAD DE SUS PRINCIPALES CABECERAS - Rosalba Mancinas-Chávez; Daniel Moya-López (Cuadernos de Ilustración y Romanticismo)
In the last decades of the 19th century, the business press opened a new stage in the history of journalism. It was not only a change in management, but also a conceptual change in the way of conceiving journalism and perceiving information. This New Journalism required a strong investment, the involvement of businessmen and politicians. This fact created a network of external dependencies that compromised its independence, the germ of what we call now media structure. In the Andalusian case it was not different, a socio-economic, political and media elite was formed. This article outlines the situation of the property of the main Andalusian newspapers of the time from an unusual theoretical perspective.